Employment and Nutritional Status Among Women in Rural Nepal - M. Oddo, Vanessa; Katz, Joanne; P. West Jr., Keith; C. LeClerq, Steven; K. Khatry, Subarna (International Journal of Nutrition, 2015)
This study sought to assess the impact of part-time employment on the nutritional status of women in rural Nepal. We used longitudinal data from a prospective cohort of women in the Sarlahi District of southeastern Nepal to assess whether part-time employment was associated with a change in mid-upper-arm circumference (MUAC) between baseline and five-years. The women enrolled in the study (n =715) had applied for part-time employment distributing weekly vitamin A supplements to married women of childbearing age. Over the five-years of follow-up, women received 900 Nepalese rupees ($15 USD) per month, for approximately five hours of work per week. The women who were hired (n =324) were younger and better educated than those who were not hired (n =391), but were otherwise similar. After baseline adjustments, change in MUAC (in cm) (β = 0.08; 95 % CI: -0.20, 0.36) was not associated with employment.  Also, changes in MUAC over time were inversely related to baseline MUAC, with better nourished women gaining less (MUAC of 23 - 24.99: β = -0.83; 95% Confidence Interval CI: -1.18, -0.48; MUAC of ≥ 25: β = -0.99; 95% CI: -0.99, -0.54) compared to thin women (MUAC <21). In this sample, women employed part-time did not have improved nutritional status as compared to their unemployed counterparts. Future research should explore the impact of women’s employment on the nutritional status of other members of the household, particularly children, and among women employed full-time.
Keywords: Women’s employment; nutritional status; low- and middle-income countries